Challenges in the industrialization process of low-volume production systems - Siavash, Javadi; Jessica, Bruch; Monica, Bellgran; Peder, Hallemark (Cranfield University Press, 2013)
A critical part of new product development projects is the industrialization process of new products which affects both time and the cost. The industrialization of new products or variants in low-volume production systems has some specific challenges which are caused by characteristics of low-volume products and production systems. Therefore, an exploratory case study is made within two Swedish manufacturing companies to understand these challenges and compare the industrialization process in high and low volume production systems. The results of the multiple case studies indicate four challenges including knowledge transfer from the projects into production, development of the work instructions, the need for a higher level of training of the operators and production system design and the obligatory tailoring of the new products to the existing production systems.
Keywords: Low-volume high-variety production; production system development; industrialization